2015
DOI: 10.1016/j.cell.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation Determines PPARγ Function and Anti-diabetic Drug Response In Vivo

Abstract: SUMMARY SNPs affecting disease risk often reside in non-coding genomic regions. Here we show that SNPs are highly enriched at mouse strain-selective adipose tissue binding sites for PPARγ, a nuclear receptor for antidiabetic drugs. Many such SNPs alter binding motifs for PPARγ or cooperating factors, and functionally regulate nearby genes whose expression is strain-selective and imbalanced in heterozygous F1 mice. Moreover, genetically-determined binding of PPARγ accounts for mouse strain-specific transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 53 publications
6
113
0
Order By: Relevance
“…Indeed, PPAR␥ bound at the major Rev-erb␣ binding sites at the Klb locus in EWAT (41) (Fig. 5A, purple track).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, PPAR␥ bound at the major Rev-erb␣ binding sites at the Klb locus in EWAT (41) (Fig. 5A, purple track).…”
Section: Resultsmentioning
confidence: 99%
“…A, ChIP-seq profiles of Rev-erb␣ (green tracks, also shown in Fig. 3A) (39,48) and PPAR␥ (purple track) (41) or PPAR␣ (orange track) (42) binding at the Klb locus in, respectively, EWAT or liver of WT mice. The major Rev-erb␣ peak at the Klb locus is highlighted in pink.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple lines of evidence have shown that NC mutations can modulate the transcriptional activity and binding of key cell typespecific master transcription factors (TFs) (18,19). In several Mendelian erythroid disorders (MEDs), NC genetic variants have been identified in the DNA-binding motif (WGATAR) of the hematopoietic master regulator, GATA1 (20)(21)(22)(23)(24)(25).…”
Section: Mendelian Erythroid Disordersmentioning
confidence: 99%
“…This difficulty is most clearly reflected in the distribution of mutations listed in databases of Mendelian disorders, such as the Human Gene Mutation Database, where most mutations are found within coding regions (86%) or at intronic splice sites (11%), with only a small fraction (3%) identified in regulatory regions (14). Newer methods for annotating and predicting the impact of noncoding (NC) variants have provided substantial improvements (15, 16), but experimental validation of the presumed effects remains critical for the determination of pathogenicity and elucidation of the mechanism of action (13, 17).Multiple lines of evidence have shown that NC mutations can modulate the transcriptional activity and binding of key cell typespecific master transcription factors (TFs) (18,19). In several Mendelian erythroid disorders (MEDs), NC genetic variants have been identified in the DNA-binding motif (WGATAR) of the hematopoietic master regulator, .…”
mentioning
confidence: 99%